Impactos de filhos com deficiência intelectual na oferta de trabalho das mães no Brasil - Coutinho, Luciana Nunes (2017)
This paper aims to analyze the relationship between children’s mental illness and mother’s labor supply. Depending on the severity level of child limitation, additional care can be required; consequently, family adjustments in terms of time and money may be needed. Mothers were chosen for this study because of their role as primary caregivers for children. Using data from the Pesquisa Nacional de Saúde (PNS) - 2013, we estimated the effects of child's intellectual disability on mother's decision to work and choice of work hours. The logit and tobit models were used for a sample of women with children between 0 and 18 years old, with or without reported intellectual disability. Results suggest an average reduction of 17 percentage points in the probability of mothers work if they raise a child with intellectual disability and, if disability leads to severe limitation, the reduction may reach 25 percentage points. We also find that the child’s intellectual disability negatively and significantly affects the number of weekly work hours of mothers that are employed, with an average reduction of 8.9 hours and, in severe limitation cases, 11,2 hours. These findings are consistent with those from several international studies.